2007
DOI: 10.1158/1535-7163.mct-06-0780
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of topoisomerase IIα and G2 cell cycle arrest by NK314, a novel benzo[c]phenanthridine currently in clinical trials

Abstract: NK314 is a novel synthetic benzo[c]phenanthridine alkaloid that has recently entered clinical trials as an antitumor compound, based on impressive activities in preclinical models. The present investigations were directed at determining the mechanism of action of this agent. NK314 induced significant G 2 cell cycle arrest in several cell lines, independent of p53 status, suggesting the existence of a common mechanism of checkpoint activation. The Chk1-Cdc25C-Cdk1 G 2 checkpoint pathway was activated in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…28,29 NK314, a synthetic derivative of benzo[c]phenanthridine, is a unique anticancer agent possessing specific and potent inhibitory activity against topoisomerase II␣ (Top2␣). [30][31][32] We found that NK314 inhibited ATL cell lines with greater potency than etoposide, a Top2 inhibitor frequently used in practice. Because the range of 50% inhibitory concentration values of NK314 for ATL cell lines and non-ATL cell lines differs from those of etoposide, we investigated other targets of NK314 for induction of apoptosis and inhibition of cell growth of ATL cell lines.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…28,29 NK314, a synthetic derivative of benzo[c]phenanthridine, is a unique anticancer agent possessing specific and potent inhibitory activity against topoisomerase II␣ (Top2␣). [30][31][32] We found that NK314 inhibited ATL cell lines with greater potency than etoposide, a Top2 inhibitor frequently used in practice. Because the range of 50% inhibitory concentration values of NK314 for ATL cell lines and non-ATL cell lines differs from those of etoposide, we investigated other targets of NK314 for induction of apoptosis and inhibition of cell growth of ATL cell lines.…”
Section: Introductionmentioning
confidence: 85%
“…[30][31][32] Because NK314 inhibits Top2␣ more specifically and more potently than etoposide, which is a key drug for ATL treatment, we investigated the antitumor activity of NK314 in ATL cells. Various ATL-related (6 ATL-derived cell lines and 2 HTLV-1-infected) T-cell lines were cultured with or without IL-2.…”
Section: Nk314 Inhibited Cell Growth and Induced Apoptosis Via G 2 /Mmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) (Guo et al, 2007;Toyoda et al, 2008). The specific topoisomerase II␣-targeting activity of NK314 and lack of activity against topoisomerase II␤ distinguish its actions from other topoisomerase II inhibitors such as etoposide and doxorubicin, in that inhibition of topoisomerase II␤ is associated with secondary malignancies and toxicity (Azarova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…NK314 also showed activity toward tumors resistant to other topoisomerase II inhibitors (Onda et al, 2008). Because NK314 has been demonstrated to induce rapid and extensive DNA DSBs (Guo et al, 2007;Onda et al, 2008), further investigation of the response of DNA repair pathways to NK314 is needed to understand the cell survival and resistance mechanisms and develop mechanism-based combination strategies.…”
Section: Introductionmentioning
confidence: 99%